Job Satisfaction among Ophthalmologists in Iran - Hamideh Sabbaghi; Masomeh Kalantarion; Mehdi Yaseri; Bahareh Kheiri; Zhale Rajavi; Sare Safi (Journal of Ophthalmic & Vision Research, 2022)
Abstract Purpose: To estimate the level of job satisfaction among ophthalmologists in Iran and determine the associated factors that may impact their overall job satisfaction. Methods: In this cross-sectional study, 181 ophthalmologists (79.0% male) were interviewed by the Warr-Cook-Wall questionnaire with 7-point-Likert scale, which transformed responses from a 0 (most dissatisfied) to 100 (most satisfied). Questionnaires were randomly distributed among registered ophthalmologists at the 29 t h Annual Congress of the Iranian Society of Ophthalmology in November 2019. Satisfaction under each scale was considered as a score of > 60% of the total score. Results: A total of 181 ophthalmologists with a mean age of 47.8 ± 12.1 years and 16 ± 12 years of practice participated in the present study. They were mostly satisfied with their job as a whole (88.1%, mean score: 60.6 ± 20.7) and dissatisfied with their income (55.9%, mean score: 47.6 ± 20.3). High levels of job satisfaction was found among ophthalmologists with longer duration of practice (P < 0.001) while lower levels of satisfaction were identified among those who worked in academic centers (P = 0.004). Conclusion: In this study,high levels of job satisfaction were found among ophthalmologists with longer duration of practice while low levels of satisfaction were identified among ophthalmologists who worked in academic centers. The factors of salary and working hours accounted for the least levels of job satisfaction.